Reinventing the Geological Map: Making Geoscience More Accessible to Canadians - Clague, John; Turner, Robert; Groulx, Bertrand (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1997)
Summary Geoscientists do a good job of communicating among themselves, but are far less successful in informing others about the relevance and value of what they do. Concern for public good, as well as self interest, require that we break down the walls that isolate professional geoscientists from the rest of society. Public demand for geoscience information is huge and can be met by translating what we know into a form that is understandable and interesting to the 99% of Canadians who have no geological training. Here, we describe two innovative local map products that take geoscience information to the public, the objective being to educate and stimulate. One of the products is a full-color, jargon-free, graphics-rich poster that summarizes key earth science issues relevant to residents of Vancouver.The other product is a non traditional, posterized geological map of Vancouver. These products can serve as templates for communicating geoscience in other urban areas of Canada and elsewhere.